Adaptive Governance of Disaster Drought and Flood in Rural Areas - A. Hurlbert, Margot (Water Governance - Concepts, Methods, and Practice,, 2018)
This book provides a comparative analysis of policy instruments responding to climate change, drought and flood in relation to agricultural producers and their communities in four case study areas: Alberta, Canada, Saskatchewan, Canada, Coquimbo, Chile, and Mendoza, Argentina. Assessed through a lens of effectiveness, and adaptive governance, instruments advancing livelihood capitals of agricultural producers and identified and recommendations made to improve the suite of policy instruments are made.